Effectiveness of Mindfulness Program on Stress Reduction and Well-Being in Students in Northern Iraq High Scholars - Rozhan Ali Khdir; Yasemin Sorakın; Aşkın Kiraz (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This study investigates the effectiveness of a mindfulness training program as a strategy for alleviating academic and social pressures faced by high school students in Northern Iraq. Recognizing the detrimental effects of stress on student well-being, the research employs a quantitative approach and an experimental research design to assess outcomes. High school students often grapple with intense academic and social pressures, leading to significant stress and negative impacts on their overall well-being. Previous literature underscores the importance of addressing these stressors to enhance student health and academic performance. This study aims to evaluate the efficacy of a mindfulness training program in promoting well-being and mitigating stress among high school students in Northern Iraq. The research utilized an experimental design involving two groups of students: an intervention group that participated in a six-week mindfulness training program and a control group that did not receive any intervention. Data were collected through standardized questionnaires administered before and after the training. The quantitative nature of this study allowed for the assessment of changes in well-being and stress levels across both groups. The findings indicated a positive correlation between mindfulness and well-being within the experimental group, demonstrating significant improvements post-intervention. Conversely, the control group exhibited a decline in well-being over the same period. While mindfulness training appeared to reduce stress levels in both groups, these changes were statistically insignificant, suggesting that while mindfulness has potential benefits, further exploration is necessary to understand its impact on stress reduction. These results align with existing literature that highlights the positive effects of mindfulness on well-being among students. The study corroborates the notion that mindfulness practices can foster greater awareness and attention, contributing to enhanced student well-being. However, the lack of significant changes in stress levels prompts a recommendation for further investigation into the nuances of mindfulness and its varying effects across different populations and contexts. This study underscores the potential of mindfulness as an effective tool for enhancing student well-being in Northern Iraq. Given the limitations of a solely quantitative approach, future research should consider employing mixed methods to gain deeper insights into the subjective experiences of students and the broader implications of mindfulness training. To expand on these findings, it is essential for subsequent studies to incorporate qualitative methodologies. This would facilitate a more comprehensive understanding of how mindfulness influences students' mental health and academic performance, thus enriching the existing body of literature.